2019
DOI: 10.1039/c9nj03780b
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective deprotometalation of N,N-dialkyl ferrocenecarboxamides using metal amides

Abstract: et al.. Enantioselective deprotometalation of N,N-dialkyl ferrocenecarboxamides using metal amides.1 TOC Our attempts to deprotometalate N,N-dialkyl ferrocenecarboxamides enantioselectively by using chiral lithium or lithium-zinc dialkylamides are reported. Abstract:N,N-Diisopropylferrocenecarboxamide can be enantioselectively deprotometalated by combining butyllithium with (-)-sparteine in diethyl ether at low temperature. It is of interest to identify conditions that could allow substrates bearing more react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…By following studies on the use of chiral lithium-zinc mixed amides and combinations to reach the same goal, [33] we showed in 2019 that zinc-based in situ traps generally give better results than chlorotrimethylsilane. [34] In particular, we evidenced [Zn {(S)-PEA} 2 ], in situ prepared from ZnCl 2 • TMEDA and (S)-PEALi in a 1 : 2 ratio, as the best one to this purpose. Indeed, upon addition of (S)-PEALi (1 equiv) to a mixture of [Zn{(S)-PEA} 2 ] (1 equiv) and N,N-diisopropylferrocenecarboxamide in THF at À 70°C before slow warming to À 10°C (over 3 h) and iodolysis, the corresponding 2-iodo derivative was obtained in 96 % yield and 69 % ee.…”
Section: Figurementioning
confidence: 84%
“…By following studies on the use of chiral lithium-zinc mixed amides and combinations to reach the same goal, [33] we showed in 2019 that zinc-based in situ traps generally give better results than chlorotrimethylsilane. [34] In particular, we evidenced [Zn {(S)-PEA} 2 ], in situ prepared from ZnCl 2 • TMEDA and (S)-PEALi in a 1 : 2 ratio, as the best one to this purpose. Indeed, upon addition of (S)-PEALi (1 equiv) to a mixture of [Zn{(S)-PEA} 2 ] (1 equiv) and N,N-diisopropylferrocenecarboxamide in THF at À 70°C before slow warming to À 10°C (over 3 h) and iodolysis, the corresponding 2-iodo derivative was obtained in 96 % yield and 69 % ee.…”
Section: Figurementioning
confidence: 84%
“…This was demonstrated by Price and Simpkins who reported the asymmetric deprotolithiation of P,Pdiphenylferrocenephosphine oxide in 54% ee by using lithium bis[(S)-1-phenylethyl]amide [(S)-PEALi] in the presence of trimethylsilyl chloride as an in situ trap. 66 We recently demonstrated that the use of more efficient chiral zinc-based in situ traps could be beneficial for some substrates and managed to reach enantioenriched N,N-dialkylferrocenecarboxamides, 67 O-alkylferrocenecarboxylates 68 and Oisopropylferrocenesulfonate 55 with ee ranging from 64 to 80%. Here, we initially evaluated the use of alkyllithium•chiral diamine chelates to perform the enantioselective deprotolithiation of the substrate 2 before adding a suitable electrophile.…”
Section: Resultsmentioning
confidence: 99%
“…Mixed amido/organo lithium zincates are generally less reactive bases than lithium amide-zinc trap combinations. 43,73 Nevertheless, in order to reduce competitive deprotonation by the chiral ferrocenyldiamidozincates formed during these reactions, we tested lower temperatures. However, by using (endo-S)3ZnLi [59][60][61] at -30 °C, 1-I was formed with a yield of 77% and an ee of 39% in favor of the RP enantiomer, a result similar to that obtained at rt.…”
Section: Study Using Lithium-zinc Amides Prepared From a Chiral Amine...mentioning
confidence: 99%
“…85,86 We realized in 19 2019 that, while chlorotrimethylsilane is often used as an in situ trap in deprotolithiation reactions using hindered lithium amides, 44 its ability to intercept lithium species is low compared to other traps such as ZnCl2•TMEDA and Zn(TMP)2. 73 As a consequence, this was no surprise when we tested chlorotrimethylsilane as an in situ trap in the reaction between 1-H and LiTMP in THF at -30 °C: poor results were obtained due to the degradation before trapping of the ferrocenyllithiums formed (not shown).…”
mentioning
confidence: 99%